(untitled) (Journal of the College of Basic Education, 2022)
In the present work, we have measured the radon gas concentration in nine cement samples available from the local markets, and from different countries like, (Iraq ,China , Egypt ,Lebanon, India ,Iran, AL-Saudia,Jordan and Turkyi) by using alpha-emitters registrations which are emitted from radon gas in (CR-39) nuclear track detector. The results obtained have shown that the highest average radon gas concentration in cement samples which was (199.99 Bq/m3) origin Iran, while the lowest average radon gas concentration in cement samples which was (79.99 Bq/m3) origin Iraq .The present results show that the radon gas concentration in all cements samples is below the allowed limit from (International Commission of Radiation Protection) (ICRP) agency.